Pengaruh Organizational Citizenship Behavior Dan Employee Engagement Terhadap Kinerja Karyawan (Studi Pada Rumah Sakit Umum Daerah Cideres Kabupaten Majalengka) - Prihartini, Endah; Sudirno, Dadang; Al Kautsar, Fadia (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
The success of an elimination organization depends on effective HR management. Therefore, it is important to use the right strategy in managing human resources so that a company can achieve its goals. Based on the results of the 2023 Cideres Hospital survey on community satisfaction, service performance at Cideres Hospital is in the poor category at 35.6%, so employee performance at Cideres Hospital needs to be further improved. The research aims to find out how Organizational Citizenship Behavior and Employee Engagement impact employee performance at Cideres Regional Hospital. The quantitative method in this research uses descriptive and verification analysis. Cideres Regional Hospital has 753 employees. The sampling probability used was 100 respondents. Statistical testing of the data uses SPSS version 26 and the data analysis design uses partial and simultaneous hypothesis testing, multiple linear regression analysis, coefficient of determination analysis, and classical assumptions. According to the partial test results, it can be concluded that Organizational Citizenship Behavior and Employee Engagement have a positive and significant influence on the performance of employees at Rsud Cideres. Apart from that, Organizational Citizenship Behavior and Employee Engagement have a positive and significant effect on the performance of RSUD Cideres In Majalengka Region employees simultaneously.